Human food preferences and cultural identity: The case of Aragón (Spain). (23rd August 2012) - Cantarero, Luis; Espeitx, Elena; Gil Lacruz, Marta; Martín, Pilar
<x xml:space="preserve">Abstract</x> This research aims to analyze the relationship between sociocultural values and human food preferences. The latter, as shown in this paper, are greatly influenced by cultural identity. This work stems from a theoretical context that originated in Europe and the United States towards the mid‐twentieth century, within the field of the anthropology of food. A qualitative and quantitative analysis has been performed in the Comunidad Autónoma de Aragón (Spain). Research methods include focus groups, in‐depth interviews, participant observation, and a questionnaire that was handed out to a representative sample of the Aragonese population (816 people over 21 years of age; confidence level of 95.5% and error margin of ±3.5). Regarding the research outcome, a highly significant qualitative and quantitative connection has been found between food selection and cultural identity. In other words, people prefer to consume foods that are symbolically associated with their own culture, in order to reinforce their sense of belonging. Although this study has been carried out in Aragón, it is our belief that the results can be generalized to other areas. The originality and interest of our findings are notable considering that, to date, few works have analyzed the sociocultural factors motivating food behavior. Moreover, these results could be used by public and private organizations to meet objectives such as health promotion and product marketing.